The process of end-of-life care delivery to the families of elderly patients according to the Family Health Strategy Cuidar de familias de ancianos en final de vida en la Estrategia Salud de la Familia Cuidar de famílias de idosos em final de vida na Estratégia Saúde da Família - Lucía Silva; Kátia Poles; Michelle Freire Baliza; Mariana Cristina Lobato dos Santos Ribeiro Silva; Maiara Rodrigues dos Santos; Regina Szylit Bousso (Universidade de São Paulo, 2013)
OBJECTIVE: To understand the process of end-of-life care delivery to the families of elderly patients according to a Family Health Strategy (FHS) team, to identify the meanings the team attributes to the experience and to build a theoretical model. METHOD: Symbolic Interactionism and Grounded Theory were applied. Fourteen professionals working in an FHS located in a country town in the state of São Paulo were interviewed. RESULTS: Through comparative analysis, the core category overcoming challenges to assist the family and the elderly during the dying process was identified, and it was composed of the following sub-processes: Identifying situational problems, Planning a new care strategy, Managing the care and Evaluating the care process. CONCLUSION: the team faces difficulties to achieve better performance in attending to the biological and emotional needs of families, seeking to ensure dignity to the elderly at the end of their lives and expand access to healthcare. OBJETIVO: comprender, por medio del equipo de la Estrategia Salud de la Familia (ESF), el proceso de cuidar de familias con ancianos que se encuentran en situación de final de vida, tratamos de identificar los significados que el equipo atribuye a la experiencia y con ellos construir un modelo teórico. MÉTODO: se utilizó el interaccionismo simbólico y la teoría fundamentada en los datos. Fueron entrevistados 14 profesionales de la ESF de un municipio del interior del estado de São Paulo. RESULTADOS: el análisis comparativo identificó la categoría central "superando los desafíos para acoger a la familia y al anciano durante el proceso de morir", compuesta por los subprocesos: Identificando la problemática de la situación, Planificando una nueva estrategia para el cuidar, Manejando el cuidado y Evaluando la trayectoria de cuidado. CONCLUSIÓN: el equipo enfrenta dificultades para alcanzar un mejor desempeño, acogiendo las necesidades biológicas y emocionales de las familias y buscando ofrecer dignidad a los ancianos en situación de final de vida, ampliando el acceso a la salud. OBJETIVOS: compreender o processo de cuidar de famílias de idosos em situação de final de vida para a equipe da Estratégia Saúde da Família (ESF), identificar os significados que a equipe atribui à experiência e construir um modelo teórico. MÉTODO: utilizaram-se o interacionismo simbólico e a teoria fundamentada nos dados. Foram entrevistados 14 profissionais da ESF de um município do interior paulista. RESULTADOS: a análise comparativa identificou a categoria central superando os desafios para acolher a família e o idoso durante o processo de morrer, composta pelos subprocessos: identificando a problemática da situação, planejando uma nova estratégia para o cuidar, manejando o cuidado e avaliando a sua trajetória de cuidado. CONCLUSÃO: a equipe enfrenta dificuldades para alcançar melhor desempenho, acolhendo as necessidades biológicas e emocionais das famílias e buscando oferecer dignidade aos idosos em situação de final de vida, ampliando o acesso à saúde.